From Social Media to Peer Review: How Can we Evaluate Medical Content for Misinformation and Bias? (Canadian Eye Care Today, 2023)
Traditionally, ophthalmologists stay current by referring to peer reviewed papers found on scientific databases, such as PubMed, where rigorous publication standards reduce the potential for bias. We now access medical information from diverse online sources and social media allowing for fast-paced dissemination of content. Access to this rapidly evolving online information has allowed us to be more versed in our specialized knowledge than ever before. However, the rise of social media use in medicine may challenge the traditional methods aimed to limit misinformation and bias. How can we identify and evaluate bias when we access information from multiple disparate online sources in 2023?